1998
DOI: 10.1063/1.120733
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of NH3 as nitrogen source for GaN molecular beam epitaxy

Abstract: We show that optical reflectivity measurements can be used to evaluate the part of a NH3 flux which reacts with a Ga-terminated GaN surface or with a Ga-flux simultaneously impinging on the surface, as in standard molecular beam epitaxy situation. At least for temperatures not exceeding 700 °C, the ratio of the reacted part of the NH3 flux to the incident flux can be assimilated to the NH3 cracking efficiency. Being nearly zero below a threshold temperature of 450 °C, it increases with temperature but remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 11 publications
1
77
0
Order By: Relevance
“…At lower substrate temperatures (450 C) the RHEED pattern changes to (11). It has been shown that at this temperature and below, the cracking efficiency of ammonia becomes insignificant [20]. Therefore, we assign this surface phase as (11)-N. We speculate that this phase is linked to the non-dissociative adsorption of NH 3 molecules, while the hightemperature (11)-N phase presumably results from dissociative chemisorption of NH 3 leading to the formation of NH 2 and/or NH chemisorbed radicals.…”
Section: Resultsmentioning
confidence: 99%
“…At lower substrate temperatures (450 C) the RHEED pattern changes to (11). It has been shown that at this temperature and below, the cracking efficiency of ammonia becomes insignificant [20]. Therefore, we assign this surface phase as (11)-N. We speculate that this phase is linked to the non-dissociative adsorption of NH 3 molecules, while the hightemperature (11)-N phase presumably results from dissociative chemisorption of NH 3 leading to the formation of NH 2 and/or NH chemisorbed radicals.…”
Section: Resultsmentioning
confidence: 99%
“…At 500 1C, the growth rate decreased compared with other samples grown with the same V/III ratio. This indicates the lack of reactive nitrogen, which is caused by the sharp drop of the reaction efficiency of ammonia between 600 and 500 1C [4]. TMIn is decomposed completely at temperatures above 400 1C [11].…”
Section: Methodsmentioning
confidence: 99%
“…The growth temperature is limited from above by the desorption of nitrogen and thermal decomposition of the films [3]. From below the growth temperature is limited by low thermal decomposition rate of ammonia (NH 3 ) [4], so a high V/III ratio is needed. The formation of metallic indium is a well-known problem caused by either the lack of reactive nitrogen or the desorption of nitrogen [5].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the amount of nitrogen active species is a function of the substrate temperature. For instance, it has been reported that the decomposition of NH 3 below 450°C is insignificant [5]. When increasing the substrate temperature, the NH 3 efficiency increases too but remains rather low (4 % at 700°C).…”
Section: Resultsmentioning
confidence: 99%